Faktor penyebab kemasukan semula ke Hospital Universiti Sains Malaysia (HUSM) dalam kalangan pesakit dengan penyakit Chronic Obstructive Pulmonary Disease (COPD) - Azmi, Barkhis (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
The readmission to the hospital is a serious problem for the health care system. It is an important indication of the quality and effectiveness of health care services. It is also the factor which causes increase in the cost of the health care services. Literature review shows that Chronic Obstructive Pulmonary Disease (COPD) is one of the diseases which has high readmission rates. The objective of this study is to identify the causative factor of hospital readmission among COPD patients. The identification of the factor can help to determine the action needed to reduce the number of COPD patients who have been readmitted. Reduction in the number of patients who have been readmitted will also reduce the burden of this phenomenon to the hospital and the individual who is involved. A descriptive study about the causative factor of the hospital readmission among COPD patients has been done in medical ward HUSM from 15th of December 2005 to 1 th of January 2006. There are 30 patients who have been chosen by using the convenience sampling to join this study. There are 19 male patients and I 1 female patients who have been diagnosed to have COPD and readmitted during this study. This study found that older patients especially those aged 65 years and above, male, with low education level and work as farmers are the demography factors which cause the readmission of these patients into the hospital. This study also found that patient's knowledge about the disease and treatment and the patient's inhaler administration technique shows significant association to the readmission rates with the p value for each of them is 0.000 and 0.021 respectively. While patient's compliance to the medication do not shows significant association to the readmission rates. The readmission of COPD patient which results from the exacerbation or complication of the disease are the problems which needs an attention as it has negative effect to the health institution, family and the patients themselves. Therefore, the finding of this study can be applied in the discharge plan for COPD patient in order to reduce the readmission rates and furthermore to increase the effectiveness of health care services and the patient's quality of life.